2023
DOI: 10.3390/molecules28104042
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum NKK20 Alleviates High-Fat-Diet-Induced Nonalcoholic Fatty Liver Disease in Mice through Regulating Bile Acid Anabolism

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most prevalent chronic disease in modern society. It is characterized by an accumulation of lipids in the liver and an excessive inflammatory response. Clinical trials have provided evidence that probiotics may prevent the onset and relapse of NAFLD. The aim of this study was to explore the effect of Lactiplantibacillus plantarum NKK20 strain (NKK20) on high-fat-diet-induced NAFLD in an ICR murine model and propose the underlying mechanism whereby NKK20 protects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Probiotic bacteria belonging to Lactiplantibacillus plantarum generally have several properties that can be predicted by the presence of the corresponding genes. These are, in particular, genes involved in the synthesis of bacteriocins [ 52 ], metabolism [ 53 ], conjugation of unsaturated fatty acids [ 54 ], production of biologically active peptides [ 55 ], and genes encoding exopolysaccharides [ 56 ]. In addition, genome-based safety analysis may help to identify potential risk factors for candidate probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic bacteria belonging to Lactiplantibacillus plantarum generally have several properties that can be predicted by the presence of the corresponding genes. These are, in particular, genes involved in the synthesis of bacteriocins [ 52 ], metabolism [ 53 ], conjugation of unsaturated fatty acids [ 54 ], production of biologically active peptides [ 55 ], and genes encoding exopolysaccharides [ 56 ]. In addition, genome-based safety analysis may help to identify potential risk factors for candidate probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, short-chain fatty acids (SCFAs) as the metabolites of bacterial fermentation of intestinal dietary fiber, are the key factors in inhibiting NAFLD progression through portal vein branches [ 5 ]. Numerous studies have shown that SCFAs exerted a wide spectrum of positive effects.…”
Section: Introductionmentioning
confidence: 99%